Models of Segregation - Schelling, Thomas C. (American Economic Review, 1969)
The memorandum is about the segregation that can result from discriminatory individual behavior. It examines some of the individual incentives, and perceptions of difference, that can lead collectively to segregation. It also examines the extent to which inferences can be drawn, from the phenomenon of collective segregation, about the preferences of individuals, the strengths of those preferences, and the facilities for exercising them.